Significance of Charcot Leyden crystals in liver cytology—A case report. Issue 5 (28th October 2014) - Thakral, Divya; Agarwal, Pallavi; Saran, Ravindra Kumar; Saluja, Sundeep
Abstract : Charcot Leyden crystals are colorless, hexagonal, bipyramidal crystals formed from aggregation of material from disintegrating eosinophils. Eosinophilic infiltrate along with the presence of Charcot Leyden crystals is an indirect evidence of parasitic infestation. Here, we report a case where fine‐needle aspiration cytology smears prepared from hepatic space occupying lesion showed numerous Charcot Leyden crystals along with eosinophilic infiltrate, indicating parasitic infection. Diagn. Cytopathol. 2015;43:392–394. © 2014 Wiley Periodicals, Inc.